Metamorphism on Chromite Ores from the Dobromirtsi Ultramafic Massif, Rhodope Mountains (SE Bulgaria) - J.M. GONZÁLEZ JIMÉNEZ; T. KERESTEDJIAN; J.A. PROENZA FERNÁNDEZ; F. GERVILLA LINARES (Geologica Acta, 2009)
Podiform chromitite bodies occur in highly serpentinized peridotites at Dobromirtsi Ultramafic Massif (Rhodope Mountains, southeastern Bulgaria). The ultramafic body is believed to represent a fragment of Palaeozoic ophiolite mantle. The ophiolite sequence is associated with greenschist - lower-temperature amphibolite facies metamorphosed rocks (biotitic gneisses hosting amphibolite). This association suggests that peridotites, chromitites and metamorphic rocks underwent a common metamorphic evolution. Chromitites at Dobromirtsi have been strongly altered. Their degree of alteration depends on the chromite/silicate ratio and to a lesser extent, on the size of chromitite bodies. Alteration is recorded in individual chromite grains in the form of optical and chemical zoning. Core to rim chemical trends are expressed by MgO- and Al2O3- impoverish-ment, mainly compensated by FeO and/or Fe2O3 increases. Such chemical variations correspond with threemain alteration events. The first one was associated with ocean-floor metamorphism and was characterized by alizardite replacement of olivine and the absence of chromite alteration. The second event took place duringgreenchist facies metamorphism. During this event, MgO- and SiO2- rich fluids (derived from low temperatureserpentinization of olivine and pyroxenes) reacted with chromite to form chlorite; as a consequence, chromitebecame altered to a FeO- and Cr2O3- rich, Al2O3- poor chromite. The third event, mainly developed during lowertemperature amphibolite facies metamorphism, caused the replacement of the primary and previously alteredchromite by Fe2O3- rich chromite (ferritchromite).